Method development and validation of HPLC tandem/mass spectrometry for quantification of perindopril arginine and amlodipine besylate combination in bulk and pharmaceutical formulations - Duraisamy, Kalaiyarasi (Res Pharm Sci, 2017)
A well-characterized and fully validated ultra-high performance liquid chromatography-electrospray ionization-tandem mass spectrometric (UHPLC-ESI-MS/MS) method was developed to reliably analyze combination of perindopril arginine and amlodipine besylate in bulk and tablet formulations. The chromatographic separation was achieved on a Waters ACQUITY UPLC(®) BEH C18 column with 1.7 μm particle packing which enabled the higher peak capacity, greater resolution, increased sensitivity, and higher speed of analysis using a volatile mobile phase ideally being at least 2 pH units below and above the perindopril arginine and amlodipine besylate pKa, respectively. Mass spectrometric detection was performed using electrospray ion source in positive ion polarity to profile the abundances of perindopril arginine and amlodipine besylate, using the transitions m/z 369 → m/z 172, and m/z 409 → m/z 238 for perindopril arginine and amlodipine besylate, respectively. Calibration curve was constructed over the range 0.25 – 500 ng/mL and 1.0 – 100 ng/mL for perindopril arginine and amlodipine besylate, respectively. The method was precise and accurate, and provided recovery rates > 80% for both compounds. Furthermore, the intra- and inter-assay precision in terms of % RSD was in between 0.1 – 3.7 for both perindopril arginine and amlodipine besylate. A specific, accurate, and precise UHPLC-MS/MS method for the determination of perindopril arginine and amlodipine besylate in bulk and tablet formulation.